Peningkatan Hasil Belajar IPA Melalui Penerapan Model Pembelajaran Student Team Achievement Division (STAD) - Ansori, Ahmad; Sabrifha, Eli; Junadi, Moh (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
The improvement of science learning outcomes has become a primary focus in the learning process. A strong understanding of science concepts is crucial in forming the foundational knowledge of students. However, some students still face difficulties in mastering the science materials delivered by teachers in the classroom. This Classroom Action Research (CAR) aims to enhance science learning outcomes for fourth-grade students at SD Islam Al-Husniah Pulau Kijang through the implementation of the Cooperative Learning model, specifically the Student Team Achievement Division (STAD) type. The research was conducted in two cycles, with each cycle involving planning, implementation, observation, and reflection. The results show that in the first cycle, 78% of students achieved the learning objectives, while 22% had not yet met the learning goals. In the second cycle, the results improved, with 91% of students achieving the learning objectives, and only 9% not meeting the pre-established minimum passing grade. Based on these findings, it can be concluded that the Cooperative Learning model with the STAD type can improve science learning outcomes for fourth-grade students at SD Islam Al-Husniah Pulau Kijang.